Beyond JSON: evaluating serialization formats for space-efficient communication - Maltsev, Eduard; Muliarevych, Oleksandr (Видавництво Львівської політехніки, 2024)
Distributed systems rely on efficient inter-service communication, heavily impacted by data transmission costs. This study investigates alternative serialization formats, like Avro and MessagePack, to reduce data size compared to the common JSON format. We utilize a custom model to comprehensively assess the space efficiency of serialization formats across various data types. Our findings demonstrate that adopting alternative formats achieves a median reduction in serialized data exceeding 30 %. Notably, Avro exhibits exceptional efficiency, leading to reductions exceeding 83 % in specific scenarios. These insights empower developers to select optimal formats, potentially leading to significant improvements in data transfer speed, reduced bandwidth consumption, and enhanced scalability for handling larger data volumes within distributed systems.
Keywords: Data communication; Encoding; Information exchange; Protocols; Performance evaluation